FLAVIIR, An innovative university/industry research program for collaborative research and demonstration of UAV technologies - Fielding, J. P.; Smith, Howard (International Council of the Aeronautical Sciences (ICAS), 2006)
A major research programme into advanced technologies for Uninhabited Airborne Vehicles (UAVs) in June 2004. The £6.5M, five-year project represents a major investment in aerospace technology for BAE SYSTEMS and their partner, the Engineering and Physical Sciences Research Council (EPSRC). The focus of “FLAVIIR” is to develop technologies which support low cost (to acquire and operate) UAVs, together with the broader goal of improving the exploitation and hence impact of the research work completed through closer management of the research team. The project involves ten universities working together at two levels: inter-university collaboration within disciplines and interdisciplinary collaboration both within and across university boundaries. This aspect makes the project particularly challenging for Cranfield, as it is managing the complete project (with BAE Systems) and is to deliver the benefits of these joint activities. This work leads to the integration of the technologies into a sophisticated flying demonstrator UAV which is scheduled to fly in 2009. A particularly challenging requirement is that the vehicle should demonstrate an entire flight cycle, without the use of conventional flap-type control surfaces. The project now has more than 35 researchers working in subject areas ranging from novel aerodynamic techniques to develop control forces, novel flight control systems, to hybrid laser techniques to ‘write’ sensors and actuators directly onto carbon composite structures. The paper gives a description of the new technologies being developed, their integration into a number of demonstrations and the plans for their culmination in the Demon flying demonstrator vehicle, which will be based on the Eclipse Vehicle. The paper will also discuss the equally important issues of integrating, a multi-university/Industry research team.
Keywords: Aircraft Design; UAV; Research; Advanced Technologies